Love Hate Relationship: Kebijakan Amerika Serikat Memberikan Bantuan Luar Negeri Kepada Meksiko Dalam Rangka Pemberantasan Drugs Trafficking Organizations - Fallah, Giri Afif; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The United States and Mexico, as countries that have direct borders, of course, the two countries, both the United States and Mexico, are indirectly affected by the impact of longstanding drug cartels in Mexico. Various kinds of foreign aid has been given by the United States to Mexico, one of which is the Merida Initiative. The Merida Initiative is foreign aid for Mexico in dealing with the Drugs trafficking aid organizations that include the funds, training both in legal and military terms. But seeing the relationship between the two countries can be said Love Hate Relationship, this relationship is described as the two countries still providing assistance to each other, but on the other hand the relations between the two countries are not always good, there are many conflicts between the two countries. In this paper, it will explain why the United States provides very serious foreign assistance to Mexico to deal with Drugs trafficking organizations and in answering researchers will use the concept of Human Security which later this concept will answer rational reasons why the United States provides foreign assistance to Mexico and finally the reasons will be explained are divided into two factors namely security seen from the side of National Security America and from the economic side where Mexico is an important economic partner for the United States.